2006
DOI: 10.1149/1.2359700
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Plasma and Warm Nitric Acid Surface Activation for Low-Temperature Wafer Bonding

Abstract: In this paper, the void formation and the surface energy for low-temperature Si-Si wafer bonding technique as a function of the annealing time and temperature as well as warm nitric acid and O 2 -plasma-assisted surface pretreatments are considered and compared. The analysis of the surface energy vs annealing time exhibits two main bonding mechanisms: ͑i͒ rapid reaction between silanol groups which leads to a quick enhancement of the bonding strength, and ͑ii͒ slow further increase of bonding strength and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…There are many other papers concerning plasma activated wafer bonding, typically reporting on a new plasma generator source or an optimized set of parameters [18][19][20][21]41,50,52,64,65,67,[87][88][89][90][91][92][93][94][95][96][97][98][99][100] that allow for high strength bonding at low annealing temperatures and with minimal annealing voids. A significant number of these results are applicable only to the precise experimental setup of the reporting authors or are simply unrepeatable.…”
Section: Q50mentioning
confidence: 99%
“…There are many other papers concerning plasma activated wafer bonding, typically reporting on a new plasma generator source or an optimized set of parameters [18][19][20][21]41,50,52,64,65,67,[87][88][89][90][91][92][93][94][95][96][97][98][99][100] that allow for high strength bonding at low annealing temperatures and with minimal annealing voids. A significant number of these results are applicable only to the precise experimental setup of the reporting authors or are simply unrepeatable.…”
Section: Q50mentioning
confidence: 99%
“…11a). Many published articles [12][13][14][15] have reported that O 2 plasma activation alters the native oxide surfaces in the following ways: (1) removing organic contaminants, (2) increasing in the density of silanol groups (Si-OH) on oxide surfaces, and (3) creating subsurface reservoir (i.e., porous oxide layers, like a sponge) for water molecules, which may improve the low-temperature diffusivity of water molecules at the interface. After O 2 plasma treatment, the surface is very hydrophilic so that many water molecules are more easily adsorbed on the surface when it is exposed to moderately humid air (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some small initial voids become to disappear at 8000C. It means no potential annealing voids would be generated continuously in longer heating time or higher temperature [11]. The remained voids at 8000C are mainly trapped voids, which is caused by initial particulates in our class 10 K clean room [ Fig.…”
Section: Formation Ofannealing Voids In Heating Processmentioning
confidence: 99%